(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Child sexual abuse is a major social problem across the world. According to National Crime Report Bureau report 2019 1, 48,185 crime cases against children were recorded in India. The crime rate has increased by 4.5 percent as compared to 2018. Child sexual abuse is a massive challenge for public health, social justice, human rights, gender equality, and science. There is a big silence associated with child sexual abuse. Still CSA is a taboo in our society. India is facing a steady rise in cases of sexual abuse due to the absence of adequate knowledge on this issue. Educating the stakeholders by awareness programs is the main prevention strategy. Prevention strategy is moving away from individual to adult, community, society. Several organizations today utilize social media campaigns in their vision to protect children from sexual abuse. Social media campaigns are increased and designed to increase the awareness of CSA and to break the silence associated with CSA. This study is on social media campaigns and using social media in creating awareness and prevention of child sexual abuse.